2022
DOI: 10.1101/2022.05.13.22275065
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Food Security after Nuclear Winter: A Preliminary Agricultural Sector Analysis for Aotearoa New Zealand

Abstract: We aimed to estimate the dietary energy content of food exports in the business-as-usual situation for Aotearoa New Zealand (NZ) and then its contribution to food security after a potential nuclear war-induced “nuclear winter”. From published sources we estimated dietary energy available from the major domains of food exports, with adjustments for wastage. We specifically considered a severe case nuclear winter model by Xia et al (2021) ie, 150 Tg of soot ejected into the stratosphere. We found that the curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…But other considerations for island refuge location are the findings of simulation studies of the global climate impacts of nuclear war (see “ Introduction ” section), and the risk of islands being directly attacked in a nuclear war (e.g., those in military alliances with nuclear weapon states such as Australia, Iceland and Japan). Other relevant features of island refuges include excess food production capacity 8 , 53 , capacity to survive extreme pandemics 18 , and to have the socio-economic and technological characteristics to be a “node of persisting complexity” 17 .…”
Section: Discussionmentioning
confidence: 99%
“…But other considerations for island refuge location are the findings of simulation studies of the global climate impacts of nuclear war (see “ Introduction ” section), and the risk of islands being directly attacked in a nuclear war (e.g., those in military alliances with nuclear weapon states such as Australia, Iceland and Japan). Other relevant features of island refuges include excess food production capacity 8 , 53 , capacity to survive extreme pandemics 18 , and to have the socio-economic and technological characteristics to be a “node of persisting complexity” 17 .…”
Section: Discussionmentioning
confidence: 99%
“…The 1980s models indicated that pasture growth might reduce by 34-66% in spring months according to location, or by 19-36% for the year (Green, 1989). However, this would not reduce New Zealand's food production below 2,200 kcal/capita/day, given baseline DEP of 9,570 kcal/capita/day (Schramski et al, 2019), including currently exported food totalling at least 8,150 kcal/capita/day (accounting for wastage) (Wilson et al, 2022). Diverted export dairy alone (eg, milk powder, cheese and butter) could provide 142% of dietary energy requirements in a 150 Tg scenario (Wilson et al, 2022).…”
Section: Case Study: New Zealandmentioning
confidence: 99%
“…This modelling covered most countries in the world, modelled crops and marine sh, and modelled six nuclear winter scenarios ranging from 5 Tg to 150 Tg. We identi ed all the island nations in Xia et al's analysis, and then obtained independent assessments of baseline dietary energy production (DEP) from two sources (1) peer-reviewed analysis of global food production, namely 2013 DEP (Schramski et al, 2019), and (2) our own bottom-up calculation of DEP for New Zealand exports using the Statistics New Zealand Harmonised System for export data (Wilson, Prickett, & Boyd, 2022). We then applied the modelled calorie reduction (%) results obtained by Xia et al for the major crops and marine sh averaged over the rst ve years for 5, 27 and 150 Tg nuclear war scenarios, to these independent estimates of DEP.…”
Section: Food Self-su Ciency Threshold Analysismentioning
confidence: 99%
“…The 1980s models indicated that pasture growth might reduce by 34-66% in spring months according to location, or by 19-36% for the year (Green, 1989). However, this would not reduce New Zealand's food production below 2,200 kcal/capita/day, given baseline DEP of 9,570 kcal/capita/day (Schramski et al, 2019), including currently exported food totalling at least 8,150 kcal/capita/day (accounting for wastage) (Wilson et al, 2022). Diverted export dairy alone (eg, milk powder, cheese and butter) could provide 132% of dietary energy requirements in a 150 Tg scenario (Wilson et al, 2022).…”
Section: Case Study: New Zealandmentioning
confidence: 99%
“…This modelling covered most countries in the world, modelled crops and marine sh, and modelled six nuclear winter scenarios ranging from 5 Tg to 150 Tg. We identi ed all the island nations in Xia et al's analysis, and then obtained independent assessments of baseline dietary energy production (DEP) from two sources (1) peer-reviewed analysis of global food production, namely 2013 DEP (Schramski et al, 2019), and (2) our own bottom-up calculation of DEP for New Zealand exports using the Statistics New Zealand Harmonised System for export data, in which we converted export tonnage into food energy availability, accounting for published estimates of wastage (Wilson, Prickett, & Boyd, 2022). We then applied the modelled calorie reduction (%) results obtained by Xia et al for the major crops and marine sh averaged over the rst ve years for 5, 27 and 150 Tg nuclear war scenarios, to these independent estimates of DEP.…”
Section: Food Self-su Ciency Threshold Analysismentioning
confidence: 99%